Impressive 1D (Ferrocenyl⋯C6F5R⋯)n Stacking Due to Cooperative Interactions in N-(Ferrocenylmethyl)Pentafluorobenzenecarboxamide: Four Crystal Structures and Contacts Analyses in N-(Ferrocenylalkyl)Benzenecarboxamides - John F. Gallagher; Christian Jelsch; Peter T. M. Kenny; Alan J. Lough (Crystals)
The crystal structures, interactions, and contacts analyses of four N-(ferrocenylalkyl)benzene-carboxamide derivatives are described as the N-(ferrocenylmethyl)benzenecarboxamide 4a, N-(ferrocenylmethyl)-2,6-difluorobenzenecarboxamide 4e, N-(ferrocenylmethyl)pentafluorobenzenecarboxamide 4f and N-(ferrocenylethyl)-4-fluorobenzenecarboxamide 5. Intermolecular amide⋯amide hydrogen-bonding interactions as 1D intermolecular chains are present in all four crystal structures, with N⋯O distances ranging from 2.819 (2) to 2.924 (3) Å. Three of the crystal structures have one molecule per asymmetric unit, except the phenyl 4a, which has Z’=2. In the structure of 4a, Fc(C-H)⋯(phenyl) and phenylC-H⋯π(C5H4) ring interactions dominate the interaction landscape, together with (1:1) face-to-face (phenyl)⋯(phenyl) and (C5H5)⋯(C5H5) ring stacked pairs (Fc = ferrocenyl moiety). In 4e, interlocking ferrocenyls, short C-H⋯(C-F) and C-H⋯O hydrogen bonds are the only additional notable intermolecular interactions. In the pentafluorophenyl derivative 4f, a remarkable selection of interactions is present with interwoven 1D ferrocenyl⋯(C6F5) stacking and C-H⋯F interactions; molecules aggregate forming impressive 1D columns comprising intertwined (Fc⋯C6F5⋯)n ring stacking. In the ethyl bridged system 5, C-H⋯F and C-H⋯π (arene) contacts with (4-fluorobenzene) ring⋯ring pairs combine and stack about inversion centres. The reported para-F substituted structure REYWOU (4d) is used for comparisons with the 4a, 4e, 4f, and 5 crystal structures. In view of the rich interaction chemistry, contacts enrichment analyses of the Hirshfeld surface highlights several interesting features in all five ferrocenylalkylcarboxamide structures.